y = f(x)
let P(7,-6) be a point on the curve
we know that that the gradient of the tangent to the curve at P is 4 (g'(7) = 4 stated)
( y -b) = (dy/dx)k (x-a)..............(1)
where (dy/dx)k denotes the value of dy/dx when a is substituted for x
here we have a = 7, b = -6 and (dy/dx)k = 4
substitute these values into (1), we have
y-(-6) = 4(x-7)
y+6 = 4x -28 >>>>>>> y = 4x-34
therefore,the equation to the tangent line to the graph of y = g(x) at the point (7,-6) is y = 4x-34
2006-10-07 08:12:22
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
The polymomial in any case of a 2d order to have a tangenent enable us take second order there are a variety of of varieties. we may be able to pick g(x)= ax^2+bx+c at x =7 g(x) = -6 or -6 = 49a + 14b + c g'(x) = 2ax + b so 4 = 14 a +b or b = 4- 14 a so equtation of tangent for above sort is 2ax + 4 - 14a for a random a there are more suitable than one eqution won't be able to be determined as g isn't unique
2016-12-04 09:16:09
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
Since g'(7) is 4, it means that the derivative of the function g(x) at x = 7 is 4. That means, the SLOPE of the function at x = 7 is 4. It says that g(7) = -6. This means that the point (7, -6) is on the function g(x). Now you can just use the point-slope formula:
y - y1 = m(x - x1)
y + 6 = 4(x - 7)
y + 6 = 4x - 28
y = 4x - 34
2006-10-07 07:08:37
·
answer #3
·
answered by عبد الله (ドラゴン) 5
·
1⤊
0⤋
use the slope intercept form since the slope is given: m=4
y=4x+b
we have the point 7,-6 so
-6=4*7+b
b=-6-28=-34
y=4x-34
2006-10-07 06:53:50
·
answer #4
·
answered by yupchagee 7
·
1⤊
0⤋
I hate trigonometry... am having a flashback of teacher Dilsa explaining that,... god I hate that subject!!!!
2006-10-07 16:20:27
·
answer #5
·
answered by Repostera06 6
·
0⤊
1⤋
uhm
2006-10-08 08:02:57
·
answer #6
·
answered by CHARMIN 1
·
0⤊
0⤋
i have no idea
2006-10-07 06:59:28
·
answer #7
·
answered by Rebekah A 1
·
0⤊
2⤋
34.
BYE.
2006-10-08 05:26:08
·
answer #8
·
answered by CrAzY aNd InLoVe FaIrY :-) 6
·
0⤊
1⤋